STUDY ON VACCINE COLD CHAIN MANAGEMENT ROUTINE IMMUNIZATION IN THE SERIBU ISLANDS DKI JAKARTA 2024 - HURIYATI (Universitas Brawijaya, 2024)
Vaccines are biological components with special characteristics and are important products in immunization programs, which are efforts to prevent diseases, disabilities, and deaths caused by vaccine-preventable diseases (VPD) in children and adults. This research study aims to benefit the advancement of immunization programs and pharmacy programs in vaccine management so that the immunization goal of enhancing the immunity of the Thousand Islands community against VPD can be achieved. Qualitative research method with a phenomenological research design, structured observation of ongoing management accompanied by interviews and document review. The research variables are cold chain equipment, temperature management, and vaccine inventory. The results of the cold chain equipment study show that 5 community health centers have conducted routine maintenance, while 2 community health centers have not conducted routine maintenance. Temperature management is carried out according to guidelines, but one health center does not record temperatures regularly. In the vaccine inventory, all health centers stored vaccines longer than the duration specified in the guidelines, and vaccines with VVM C were found in one health center. The cold chain management for routine immunization vaccines in the Thousand Islands has adequate cold chain equipment readiness.